2022
DOI: 10.1177/00202940221101675
|View full text |Cite
|
Sign up to set email alerts
|

Bi-exponential model and inverse model of magnetorheological damper for the semi-active suspension of a capsule vehicle

Abstract: The capsule vehicle is a new transportation system that travels in a sub-vacuum tunnel at a speed of about 1000 km/h, and adopts the electrodynamic suspension type levitation system. Accordingly, although it differs according to the driving speed, the vibration of capsule vehicle is expected to be greater than that of the wheel/rail type high-speed rail vehicles. Therefore, a method of applying a semi-active control technique using an MR damper as a secondary suspension of a capsule vehicle to improve passenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Therefore, it is necessary to determine the control requirements of the forward inverse models, so as to take into account the complexity of the forward model and the accuracy of the inverse model [23]. Yoon et al [24] proposed the biexponential model and its inverse model, which can be easily and simply applied to the semi-active control. It indicated that the bi-exponential model reduces about 10% more than the Bouc-Wen model by the hardware in the loop simulation test.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to determine the control requirements of the forward inverse models, so as to take into account the complexity of the forward model and the accuracy of the inverse model [23]. Yoon et al [24] proposed the biexponential model and its inverse model, which can be easily and simply applied to the semi-active control. It indicated that the bi-exponential model reduces about 10% more than the Bouc-Wen model by the hardware in the loop simulation test.…”
Section: Introductionmentioning
confidence: 99%